Health Outcomes, Public Health Spending and Education nexus in Kenya - James Murunga; Elijah Ruttoh Chebet (European Scientific Journal, ESJ, 2025)
The Sustainable Development Goal 3 requires countries to provide good health and well-being for their people through quality health care. It is therefore important for a country to have information on the right mix of public expenditure in the health sector and education quality to have better health outcomes. This study contributes to achieving Goal 3 by studying the role of government spending on the health sector and the role education quality has on health outcomes, namely the longevity and child mortality rate in Kenya. The study adopts the ordinary least squares method to estimate this relationship. This study applies time series data for a period spanning from 1990 to 2022. The results show that government spending on the health sector has statistically significant asymmetric quadratic effects on health outcomes in Kenya. Results of the study reveal that sustainable government spending on the health sector can achieve better health outcomes, as 1.31 for the child mortality rate and 1.42 for longevity or life expectancy at birth. In addition, results show that interacting government expenditure in the health sector and education quality reduces child mortality rate and also improves longevity. Lastly, the interaction term indicates that improving education quality beyond a threshold of 1.81 can reduce child mortality rate and beyond 1.99 can improve longevity. The study therefore recommends that policymakers ensure both public health expenditure and educational quality exceed the established thresholds for sustainable health outcomes in Kenya.